PSIM simulation of voltage-fed series resonant inverter for induction heating systems (Aintelia Science Notes, 2022)
In order to obtain alloys from metals or to weld in daily life, metals must be melted, rapidly heated and cooled, or partial heating must be performed. One of the effective methods used for such needs is the induction heating system. The hard-switching and soft-switching inverters are used in induction heating systems. In this study, the design and analysis of a voltage source series resonance inverter, one of the soft-switching inverters, for induction heating process has been carried out. Based on the information obtained as a result of the design, the necessary circuit elements for a series resonance inverter were determined and a simulation study was carried out with PSIM software. In the simulation study, the switching frequency is selected at different values and the response of the circuit according to the switching frequency is examined. Thus, the response of the designed series resonant inverter at the resonant frequency and outside the resonant frequency has been examined. Accordingly, the series resonance inverter designed for induction heating is capacitive when the switching frequency is below the resonance frequency, and it has been determined that switching losses occur at turn-on. In the case where the switching frequency is above the resonance frequency, it is inductive and it has been determined that the switching losses of the switches increase at turn-off. In the case where the switching frequency is equal to the resonance frequency, it is determined that soft switching occurs and maximum power transfer to the load is provided, and the simulation results obtained are presented.
Keywords: Induction Heating Systems; Series Resonance Inverters; PSIM